2019
DOI: 10.1093/ejcts/ezz138
|View full text |Cite
|
Sign up to set email alerts
|

In situ skeletonized bilateral thoracic artery for left coronary circulation: a 20-year experience

Abstract: OBJECTIVES Our goal was to analyse the outcomes in a patient population using a standardized technique for coronary artery bypass grafting (CABG) consisting of total arterial myocardial revascularization utilizing the in situ skeletonized bilateral thoracic artery for left coronary circulation. We also explored potential predictors of long-time unfavourable outcomes. METHODS Patients undergoing total arterial myocardial revas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The main aim of this study was to analyze the influence of two different CABG techniques involving the use of single or double thoracic arteries on the occurrence of post-operative ALLI in patients with PAD. The importance of PAD as a predictor of reduced long-term survival and increased risk for complications following CABG has been sufficiently documented [4,[20][21][22][23]. Any final conclusion is far from being drawn as to whether a specific technique may help in improving the outcomes and, more specifically, whether the use of the double mammary artery technique is the right choice for these patients when considering its established advantages [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this study was to analyze the influence of two different CABG techniques involving the use of single or double thoracic arteries on the occurrence of post-operative ALLI in patients with PAD. The importance of PAD as a predictor of reduced long-term survival and increased risk for complications following CABG has been sufficiently documented [4,[20][21][22][23]. Any final conclusion is far from being drawn as to whether a specific technique may help in improving the outcomes and, more specifically, whether the use of the double mammary artery technique is the right choice for these patients when considering its established advantages [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…6 In a recent study of 1325 patients who received in situ bilateral internal thoracic artery grafts to left coronary bed as a part of total arterial revascularization, the rate of graft failure after 18 years of follow-up was 1.6% for LITA, 2.9% for right internal mammary artery, and as high as 20.7% for the radial artery, which was used as a free graft to the right coronary bed. 7 Hwang and colleagues 8 reported that the use of SVG as a part of composite graft (SVG off the LITA) confers similar results as the use of multiple arterial grafts. The 10-year patency rates reported by Hwang and colleagues 8 were excellent: 96.6% in the composite SVG group and 91.4% in the multiple arterial group.…”
Section: Reply: Can You Really Turn a Vein Into An Artery?mentioning
confidence: 99%
“… 6 In a recent study of 1325 patients who received in situ bilateral internal thoracic artery grafts to left coronary bed as a part of total arterial revascularization, the rate of graft failure after 18 years of follow-up was 1.6% for LITA, 2.9% for right internal mammary artery, and as high as 20.7% for the radial artery, which was used as a free graft to the right coronary bed. 7 …”
mentioning
confidence: 99%
“…Long-term outcomes were comparable with those of other similar studies in the literature, 28-38 but, as expected, poorer than those for isolated BITA grafting. [5][6][7][8][9][10][11][12][13]15,17,27,39,40 In this series of patients with an average age of more than 70 years, approximately 50% of subjects were alive or free from MACCE at 10 years after surgery; approximately 85% of patients were free from cardiac or cerebrovascular death or from hospital readmission for CHF; approximately 97% of patients were free from PCI or cardiac reoperation; finally, approximately 95% of patients were free from cerebrovascular accident after hospital discharge. Although female sex, extracardiac arteriopathy, chronic dialysis, and poor systolic function before surgery were risk factors for both cardiac or cerebrovascular death and MACCE, active infective endocarditis and prolonged myocardial ischemia during surgery were the sole predictors of repeat operation or PCI.…”
Section: Early and Late Survival Of Patients (Only Those Frommentioning
confidence: 99%